NÃšMERO E DISTRIBUIÃ‡ÃƒO DOS ESTÃ”MATOS EM FOLHAS DE ð˜—ð˜¢ð˜¯ð˜ªð˜¤ð˜¶ð˜® ð˜®ð˜¢ð˜¹ð˜ªð˜®ð˜¶ð˜® JACQ. E ð˜—ð˜¢ð˜¯ð˜ªð˜¤ð˜¶ð˜® ð˜¤ð˜°ð˜ð˜°ð˜³ð˜¢ð˜µð˜¶ð˜® L. - Rodella, Roberto Antonio; Ayoub, Jorge Fehed; Maimoni-Rodella, Rita C. S. (REVISTA DE AGRICULTURA, 2020)
NÃšMERO E DISTRIBUIÃ‡ÃƒO DOS ESTÃ”MATOS EM FOLHAS DE ð˜—ð˜¢ð˜¯ð˜ªð˜¤ð˜¶ð˜® ð˜®ð˜¢ð˜¹ð˜ªð˜®ð˜¶ð˜® JACQ. E ð˜—ð˜¢ð˜¯ð˜ªð˜¤ð˜¶ð˜® ð˜¤ð˜°ð˜ð˜°ð˜³ð˜¢ð˜µð˜¶ð˜® L.